Measurement of P Contribution From Several P Sources by Using 32P Method - A.D. Suyono; A. Citraresmini (Atom Indonesia, 2010)
P-fertilizer other than chemical fertilizers has been used extensively in agriculture. However, the extent to which P-fertilizer contributes to the growth of plants has only been discussed a few, meanwhile the information will be very helpful to the use of P-fertilizer efficiently. The 32P method was used to distinguish P contribution from several sources, i.e soil, chemical fertilizer (Sp) and manure/organic fertilizer (Pk). The isotope carrier free solution of KH232PO4, which is contained of 98% 32P, was applied to the soil and thus making it as the only source of labeled-P. Radioactivity counting of soil samples will lead to the measurement of P-contribution from several sources of P given. The experiment result showed that most of the P taken up by the plants was from soil. Thus, the P from Sp (P-Sp) and Pk (P-Pk) became un-significantly support the plant growth expressed in lesser dry weight of straw, grain and plants compared to those who taken its P from soil. Although soil contributed most of its available P to straw and grain of lowland rice, but Sp and Pk still contributed P to both plant parts. It was obtained that in straw 64 – 82% P was derived from soil; 12 – 21% P was derived from Pk; and 18 – 29% P was derived from Sp. For grain 49 – 89% P was derived from soil; 11 – 15% P was derived from Pk; and19 – 45% P was derived from Sp. Received: 20 November 2009; Revised: 09 August 2010; Accepted: 23 August 2010